Futures in the present: Unraveling foreclosing and pre-opening desired futures in the local environment with a Bourdieusian perspective. (May 2023) - Veenman, Sietske; Kaufmann, Maria; Haarbosch, Simone
Abstract: Citizens are considered to play an increasingly active role in dealing with sustainability challenges, such as biodiversity loss. The active involvement of citizens is a new policy practice in the Netherlands, institutionalized in a so-called neighborhood approach. To understand why some citizens take up this role, while others face difficulties, the anticipation of futures is increasingly gaining attention in literature on sustainable transformations. Although these processes of anticipation are non-linear, literature shows that insights of Bourdieu have the potential to better understand such processes. Therefore, applying a narrative approach with walking interviews, this study innovatively combines insights from future studies (making of futures and using of futures) and the terminology as provided by Bourdieu (field, habitus and capital). The research shows two ways of how extrapolating futures lead to foreclosing a desired futures: one enacted in the habitus and one enacted in the field. The research also shows that in the process of pre-opening of futures, dynamic relations between different forms of capital are essential and that these relations are influenced by anticipation of futures: citizens whose extrapolated and desired future are aligned, whether in the field or enacted in the habitus seem to be more inclined to pre-open futures. Highlights: Future studies with insights from Bourdieu's habitus and field. How the use of futures leads to actions in the present by triggering the use (or not) of different forms of capital. Foreclosing desired futures is influenced by the anticipation of futures in the habitus (through forms of capital) and in the field. Citizens whose extrapolated and desired future are aligned, seem to be more inclined to pre-open futures. To pre-open futures, dynamic relations between different forms of capital are essential, which, in turn, are mediated by anticipation of futures.